Making the ECB the central bank of a non-federal coalition of states - Mario Tonveronachi (PSL Quarterly Review, 2015)
The recent crisis has shown that the inconsistent design of the Euro area had previously produced financial convergence, not integration. The crisis increased fragmentation thus further exposing the limits of the single monetary policy. The absence of a common fiscal authority impedes the birth of a single European financial market, which being at the centre of the European project would require financial operators to refer to a single risk-free yield curve. The recent reforms and the proposals contained in the report of the five presidents do not mark significant progresses towards making the overall design consistent with the production of the internal single financial market. We propose that by issuing debt certificates encompassing the entire maturity spectrum the European Central Bank might provide for a single risk-free yield curve. We show that the proposal is fully consistent with the current ECB’s mandate and does not require any treaty revision.